Optimization of glutathione biosynthesis in yeast: toward efficient biotechnological production of antioxidants - Starovoitova, Svitlana; Dolia, Liubov (My University, 2025)
Cell protection against reactive oxygen species is ensured by antioxidant molecules, among which the key compound is reduced glutathione (GSH). It is the most abundant non-protein thiol in cells, with a concentration of about 15 mM. Approximately 99% of it exists in the reduced form, while only about 1% is present as oxidized glutathione. The S. cerevisiae HBSD-W08 strain effectively performs GSH biosynthesis, underscoring the potential of producing a dietary supplement capable of supplying the body with sufficient amounts of this vital antioxidant. Захист клітин від активних форм кисню забезпечується антиоксидантними молекулами, серед яких ключовою сполукою є відновлений глутатіон (GSH). Це найпоширеніший небілковий тіол у клітинах, концентрація якого становить близько 15 мМ. Приблизно 99% його існує у відновленій формі, тоді як лише близько 1% присутній у вигляді окисленого глутатіону. Штам S. cerevisiae HBSD-W08 ефективно здійснює біосинтез GSH, що підкреслює потенціал виробництва харчової добавки, здатної забезпечувати організм достатньою кількістю цього життєво важливого антиоксиданту.
Keywords: кафедра біотехнології і мікробіології; тіол; глутатіон; glutathione